Scientometric approach to scientific MediSur production - Ibraín Enrique Corrales Reyes; Yasmnay Fornaris Cedeño; Juan José Reyes Pérez; Leonardo Valdés Gamboa (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2017)
Foundation: scientometric analyzes applied to scientific journals are instruments that allow evaluating their performance and impact. Objective: to evaluate the MediSur scientific production in the period 2003-2016. Methods: a scienciometric study was carried out on Medisur scientific production. The following variables were studied: publication years, total articles, citations, average citations per year, average citations by articles, average citations by authors, average citations by authors per year, average articles by author, number of citations by author (Hc), h h index, hI index, hI normalized index, AWCR index, AW index, AWCRpA index, index E, index hm, annual hI index, amplitude h, amplitude and indexation. Scientometric indicators were calculated using Harzing's Publish or Perish version 5 software, based on Academic Google. Results: the journal received 2509 citations with an average of 179.21 citations per year and has a h of 19 and a g of 34. 1000 published articles were analyzed with an average of 447, 42 articles per author and 2, 80 authors by articles; the most cited article obtained 368 citations. Conclusions: MediSur has scientiometric indicators comparable to other journals of high scientific impact. The most cited article was related to the clinical method.